The complete chloroplast genome sequence of Fargesia qinlingensis (Poaceae): an endemic to China - Ya Fu Zhou; Yu Chao Wang; Xi Lu Ni; Shao Li Mao (Mitochondrial DNA. Part B. Resources, 2018)
The complete chloroplast genome of Fargesia qinlingensis (Poaceae) has been reconstructed from the whole-genome Illumina sequencing data. The complete chloroplast genome sequence of F. qinlingensis obtained in this study was 139,640 bp in length, with a large single copy (LSC) region of 83,220 bp, a small single copy (SSC) region of 12,826 bp, separated by two inverted repeat (IR) regions of 21,797 bp each. The GC content was 38.9%, and in the LSC, SSC, and IR regions were 37.0%, 33.2%, and 44.2%, respectively. A total of 130 genes were annotated, including 83 protein-coding genes (PCGs), 39 transfer RNA (tRNA) genes, and eight ribosomal RNA (rRNA) genes. The result of the phylogenetic analysis showed that F. qinlingensis was more closely related to the species of F. denudata.